2022
DOI: 10.1055/a-1944-2686
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uromodulin in Children and Adolescents with Type 1 Diabetes Mellitus and Controls: Its Potential Role in Kidney Health

Abstract: Uromodulin is a kidney specific tubular protein and, since recently assessed in serum (sUMOD), reveals potential as a novel marker for both function and the integrity of renal parenchymal cells, and not directly depending on the glomerular filtration rate. Early diabetic nephropathy parallels glomerular hyperfiltration, often leading to diagnostic misinterpretation. Moreover, traditional kidney function markers are unsuitable to diagnose structural lesions. Recent data show that sUMOD is linked to glucose into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…PLG (plasminogen) [73], AFM (afamin) [54], AGTR1 [74] and UMOD (uromodulin) [75] might be a potential therapeutic target for sepsis. Abnormal regulation of PLG (plasminogen) [76], AFM (afamin) [77], GSTA1 [78], AGTR1 [79] and UMOD (uromodulin) [80] are associated with diabetes mellitus. PLG (plasminogen) [81] plays an indispensable role in glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…PLG (plasminogen) [73], AFM (afamin) [54], AGTR1 [74] and UMOD (uromodulin) [75] might be a potential therapeutic target for sepsis. Abnormal regulation of PLG (plasminogen) [76], AFM (afamin) [77], GSTA1 [78], AGTR1 [79] and UMOD (uromodulin) [80] are associated with diabetes mellitus. PLG (plasminogen) [81] plays an indispensable role in glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies, selected biologically active substances were indicated as contributing to the etiology (IAPP [ 16 , 31 , 32 , 33 , 34 , 35 , 36 ], proIAPP [ 17 , 18 , 37 ], I-FABP [ 24 ]), course (CST [ 38 , 39 ], ChgA [ 40 , 41 , 42 ]) or the development of various complications (neuropathy—NGF [ 43 , 44 , 45 ], cardiovascular complications—PAF [ 26 , 46 , 47 ], and cardiovascular complications and nephropatia—UMOD [ 28 , 48 , 49 ]). In the current study, we assessed the diagnostic usefulness of these indicators present in T1D patients’ sera and confirmed statistically significant differences between their concentrations in the group of children with T1D and healthy children, but only some of them (NGF, ChgA, CST and PAF) were affected by disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…We also included in our analysis substances potentially evaluable as indicators of late complications, neurological—nerve growth factor (NGF) [ 25 ], and vascular—platelet-activating factor (PAF) [ 26 , 27 ]. Finally, we assessed uromodulin, a protein secreted by the cells of the distal nephron tubules, strongly correlated with eGFR, which could be related to diabetic nephropathy in T1D patients [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children/adolescents with type 1 diabetes exhibit serum uromodulin concentrations comparable to those of healthy controls [168]. Conversely, Wiromrat et al reported reduced serum uromodulin concentrations in adolescents with type 1 diabetes compared with their non-diabetic counterparts.…”
Section: Diabetic Nephropathymentioning
confidence: 94%
“…Serum uromodulin levels seem to be associated with an increased risk of kidney tissue remodeling and potentially subsequent cardiovascular changes [168]. In type 1 diabetes, there is a pressing need for novel biomarkers that can more accurately predict coronary artery calcification (CAC), an indicator of subclinical atherosclerosis and DKD.…”
Section: Diabetic Nephropathymentioning
confidence: 99%